Efektivitas Pelaksanaan PERDA Pengelolaan Sampah di Batam Kota Terhadap Sustainable Development Goals - Alriyadi, Yan; Nurlaily, Nurlaily; Seroja, Triana Dewi (UNES Law Review, 2023)
Waste management is something that is important and needs attention. The 1945 Constitution has guaranteed the basic rights of citizens to the environment as stipulated in Article 28H paragraph (1) of the 1945 Constitution which reads "Everyone has the right to live in physical and spiritual prosperity, to have a place to live, and to have a good and healthy environment and entitled to health services”. The Batam City Government has established Batam City Regional Regulation Number 11 of 2013 concerning Waste Management as the implementing regulation of Law no. 18 of 2008 in the city of Batam. However, in reality in the field, the management and handling of waste in the city of Batam can still be said to be not optimal. Based on the data, the waste transported to the TPA (direct and indirect is 57.36% or 1,523.20 m³/day, the waste is managed independently by the community is 0.033% or 0.95 m³/day, the 3R Processed waste (TPS3R/ TPST/Waste Bank) of 0.52% or 1.45 m³/day, and Unprocessed waste of 42.56% or 1,130.04 m³/day.This research is an empirical juridical study using a sociological approach.Primary data used in this study were field studies in the form of data and interview results with the Batam City Environment Service as well as the results of interviews with some communities around the Batam Kota sub-district, and coupled with data obtained from research questionnaires which were distributed to communities around the Batam sub-district area City using random sampling method.